Does Inflation Slow Long-Run Growth in India? - Mohaddes, Kamiar (IMF Working Papers; Working Paper ;, 2014)
This paper examines the long-run relationship between consumer price index industrial workers (CPI-IW) inflation and GDP growth in India. We collect data on a sample of 14 Indian states over the period 1989-2013, and use the cross-sectionally augmented distributed lag (CSDL) approach of Chudik and others (2013) as well as the standard panel ARDL method for estimation-to account for cross-state heterogeneity and dependence, dynamics and feedback effects. Our findings suggest that, on average, there is a negative long-run relationship between inflation and economic growth in India. We also find statistically-significant inflation-growth threshold effects in the case of states with persistently-elevated inflation rates of above 5.5 percent. This suggest the need for the Reserve Bank of India to balance the short-term growthinflation trade-off, in light of the long-term negative effects on growth of persistently-high inflation.